ELECTIONS IN MADURA: BETWEEN PEACEFUL TRADITIONS AND VIOLENT PRACTICES - Fawaidi, Ach. (Universitas Al-Amien Prenduan, 2025)
Elections in Madura reveal a paradox between deeply rooted traditions of peace and recurring practices of electoral violence. While the community is often characterized by strong social solidarity, religiosity, and cultural cohesion, episodes of violence frequently accompany political contests, especially during elections. This study explores three primary factors driving electoral violence in Madura: First, the patron-client culture that enables political mobilization through influential religious and local figures (kiai and blater), Second, the transformation of traditional familial solidarity (taretan) into partisan fanaticism, resulting in social conflicts, and third, the political economy of poverty, which fosters transactional politics and vote-buying. Using a qualitative approach and secondary data sources, this article argues that such violence stems from political rivalry and entrenched social structures, economic inequalities, and weak local law enforcement. The study highlights the need to strengthen electoral institutions, improve political literacy, and engage local leaders constructively to restore a culture of peaceful and participatory democracy in Madura.